Scedosporium apiospermum in chronic granulomatous disease treated with an HLA matched bone marrow transplant. Issue 10 (1st October 2002) - Gompels, M M; Bethune, C A; Jackson, G; Spickett, G P
Abstract : A patient with chronic granulomatous disease who was being treated with steroids was diagnosed with a soft tissue Scedosporium apiospermum infection. Despite extensive treatment with antifungals progression to involve solid tissue (bone) occurred. Treatment required an HLA matched bone marrow transplant, which led to complete clearance of the fungal infection, although the patient subsequently died.